1949
DOI: 10.1139/cjr49b-049
|View full text |Cite
|
Sign up to set email alerts
|

Nitrolysis of Hexamethylenetetramine: Iii. Preparation of Pure Cyclonite

Abstract: All Cyclonite prepared by nitrolysis of hexamethylenetetramine has been found to contain 1,3,5,7-tetranitro-1,3,5,7-tetrazacycloöctatie (HMX). This impurity is not present in Cyclonite prepared by oxidation of 1,3,5-trinitroso-1,3,5-triazacyclohexane. The oxidation yields 1-nitroso-3,5-dinitro-1,3,5-triaza-cyclohexane as an intermediate. There seems then to be a difference in reactivity of two of the three aza linkages in triazacyclohexanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1959
1959
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Synthesis of TNX. Hexahydro-1,3,5-trinitroso-1,3,5-triazine (TNX) was prepared by the method of Brockman et al (3). The crude product was recrystallized twice from 95% ethanol and then from benzene to give 4.8 g of yellow needles (mp 105 to 107°C; literature 105 to 107°C).…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of TNX. Hexahydro-1,3,5-trinitroso-1,3,5-triazine (TNX) was prepared by the method of Brockman et al (3). The crude product was recrystallized twice from 95% ethanol and then from benzene to give 4.8 g of yellow needles (mp 105 to 107°C; literature 105 to 107°C).…”
Section: Methodsmentioning
confidence: 99%
“…Mono-and trinitroso-RDX derivatives were synthesized according to the methods described by Brockman et al (1949). Stock solutions of RDX and HMX, labeled and unlabeled, were prepared in acetone.…”
Section: Chemicalsmentioning
confidence: 99%
“…After the second treatment under these conditions, the desired tri-Nnitroamine (cyclonite) was formed from the di-N-nitroamine in 75% yield. 69 Interestingly, the authors reported the failure of peroxymonosulfuric acid (Caro's acid), potassium chlorate, or hypochlorite to promote the desired oxidation.…”
Section: ■ Reductive Nitrosamine Chemistrymentioning
confidence: 82%